Application of near- and mid-infrared spectroscopy combined with chemometrics for discrimination and authentication of herbal products: A review - , Abdul Rohman; Windarsih, Anjar; Hossain, M A. Motalib; Johan, Mohd Rafie; Ali, Md. Eaqub; Ahmad Fadzillah, Nurrulhidayah (Open Science Publishers LLP, 2019)
Herbal medicines along with its preparations have been commonly used as preventive and promotive agents around the world, especially in developing countries. Motivated by economic profits, the high-priced value of herbal medicines may be substituted or adulterated with less expensive ones; therefore, the authentication methods must be developed to overcome the adulteration practices. Due to their properties as fingerprint analytical techniques, near-infrared (NIR) and mid-infrared (MIR) spectroscopies offered fast and reliable techniques for authentication of herbal medicine. The data generated during authentication of herbal medicines were complex and difficult to be interpreted; therefore, the statistical approach called chemometrics has been used to treat data. The objective of the present review was to highlight the updates on the application of NIR and MIR spectroscopies and chemometrics techniques (discrimination, classification, and quantification) for discrimination and authentication of herbal medicine.